NANOEMULSION EXTRACT ETHANOL Brucea javanica (L) Merr. FORMULATION USING TWEEN 20 & TWEEN 80 AS EMULGATOR - Windah Anugrah Subaidah; Wahida Hajrin; Eskarani Tri Pratiwi; Sucilawaty Ridwan (JURNAL KATALISATOR, 2023)
Brucea javanica (L) Merr. has the potential to be developed as a topical application as a result of its high flavonoid content. However, advancements in pharmaceutical preparation are constrained by the chemicals' poor bioavailability when prepared conventionally. Nanoemulsion preparation has been an efficient method for enhancing topical preparation absorption. The previous studies show that the stable formulation of nanoemulsion depends on emulgator, especially tween. This study's objective is to create an ethanol extract of Brucea javanica (L) Merr. using tween 20 and tween 80 as emulsifying agent. A pseudo-ternary phase diagram was utilized to formulate the nanoemulsion formula. Physical characteristics such as particle size, polydispersity index, zeta potential, percent transmittance, drug load, viscosity, and pH were then analyzed for the nanoemulsion. At 15 sampling points, the formula tween 20 (surfactant):PEG 400 (cosurfactant) in a 1:1 ratio did not produce a clear preparation. In contrast, tween 80 with the same cosurfactant and ratio formed a formula that was transparent. The formula was then examined for its physical parameters, which included a particle size of 17.90.14 nm, a polydispersity index of 0.0970.012, a zeta potential of 84.63% transmittance, a drug load of 99.97%, a viscosity of 240 cp, and a pH of 7.194. According to the results, tween 80 is the most suited emulsifier for the production of Brucea javanica (L) Merr extract nanoemulsion. The study of physical attributes reveals that the nanoemulsion generated satisfies the criteria for nanoemulsions with desirable physical properties. Furthermore, the study provides data required for the development of a nanoemulsion of ethanol extract of Brucea javanica.